A simulation-based analysis to improve line throughput for high-volume manufacturing - Xia, Hua (2014)
This project investigates a production line that faces fluctuating demand with seasonal pattern. The cumulative capacity exceeds the cumulative demand in a one year period; however, its expected weekly capacity is not able to meet the weekly demand during the peak season. In addition, examining its past production outputs, there existed a large gap below the expected capacity. Therefore, it has become crucial to study the significant factors influencing the line performance.